Karakteristik Lapisan Batubara pada Cekungan Bentarsari Terhadap Pola Sebaran Di Daerah Bentar Dan Sekitarnya Kecamatan Salem Kabupaten Brebes - Nur Widi Astanto Agus Tri Heriyadi; Fivry Wellda Maulana; Alfi Firhandika (Jurnal Teknologi, Fakultas Teknologi Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2022)
The Kaliglagah Formation in the Bentarsari area, Salem District, Brebes Regency, Central Java Province is included in the Bentarsari Basin. This formation is a coal-bearing formation in the Bentarsari Basin of Late Pliocene age and is composed of layers of claystone, sandstone and coal. The coal seams in this formation were analyzed megascopically to determine the type of characteristics based on taking outcrop profiles in the research area and analyzed using the Horne classification approach, 1978 so that the depositional environment and facies of the formation of the coal seams were found. The results of the two analyzes were then used to determine the characteristics and distribution patterns of the coal seams of the Kaliglagah Formation. Characteristics The coal seam in the study area was deposited in the Crevasse splay facies, in the transitional lower delta plain depositional environment according to Horne, 1978. The distribution pattern of coal with a northwest-southeast trend, the withdrawal of coal distribution obtained three seams, namely a seam with a thickness of 1.21 m at Lp 4 , seam b with a thickness of 0.82 m on Lp 4, on Lp 2 the thickness of the coal seam is 0.03 m on seam b upper, 0.02 m on seam b middle and seam c lower 0.1 m, and 0.04 m on seam b upper and 0.03 m on seam b lower Lp 5 and seam c with a thickness of 1.65 m on seam b upper and seam c lower on Lp 1.